Patterns and correlates of caregiver satisfaction with young children's participation in home activities - Nale, Lauren Nicole, author; Khetani, Mary, advisor; Greene, David, committee member; Danhauer, Lisa, committee member; McManus, Beth, committee member (Colorado State University. Libraries, 2016)
Young children’s participation in home activities is an important indicator of their health and well-being and also facilitates development in social, physical, and emotional skills. Prior studies have shown that young children with disabilities and delays experience participation restrictions. Some young children with disabilities and delays qualify for services to improve their participation in activities. Therefore, service providers, such as occupational therapists, can benefit from context-specific information on trends and correlates of caregiver concern (i.e., dissatisfaction) with children’s participation. This detailed information can help to direct family-centered care towards improved participation. The Young Children’s Participation and Environment Measure (YC-PEM) is a caregiver questionnaire that assesses context-specific information about areas of caregiver concern (i.e., dissatisfaction) with young children’s participation in specific activities, as well as perceived environmental supports and barriers for participation in a specific setting. A recent study leveraging YC-PEM data showed that discrepancies in daycare/preschool participation between young children with and without disabilities, including caregiver desire for change (i.e., dissatisfaction), can be detected in the early childhood period. This study further leverages the YC-PEM to examine disparities in caregiver satisfaction with young children’s participation in the home. The home is a significant context given that it is where young children spend a majority of their time and where early childhood interventions often occur. Towards this end, the purpose of this study is three-fold: 1) to characterize common areas of caregiver dissatisfaction with young children’s home participation, 2) to examine common type(s) of caregiver change desired with their young child’s home participation, and 3) to evaluate child, family, and environmental correlates of caregiver dissatisfaction with young children’s participation in home activities. Study results suggest no statistically significant disability group differences in caregiver concern with young children’s participation in home-based activities. Cleaning up is the most common home activity of concern for caregivers of young children with and without disabilities or delays. Despite this commonality, caregivers of young children with disabilities or delays more often reported a desire for change in their child’s participation in non-discretionary activities, such as basic care routines and household chores. Additionally, caregivers of children with disabilities or delays most commonly desired their child to be ‘more helpful’ when participating in these non-discretionary activities. Finally, the presence of a disability or delay, annual household income of >$60,000, and lower levels of perceived environmental support were significant correlates of caregiver desire for change in young children’s participation at home. Study findings suggest that a majority of caregivers of young children with and without disabilities and delays have similar priorities for improving their child’s involvement in non-discretionary activities at home. In addition, results suggest that caregiver satisfaction with young children’s participation at home is influenced by perceptions of environmental support within the home, as well as the child’s disability status and household income. Future research should examine similar correlates of young children’s frequency and involvement in home activities, as well as desire for change in out-of-home contexts such as community. This knowledge may allow practitioners to identify appropriate intervention targets for optimizing participation in the home environment.